Pengaruh Kompetensi dan Motivasi terhadap Kinerja Karyawan Perusahaan Asuransi - Kartika Juanita Nurwin; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to explain how competence and work motivation affect employee performance in an insurance company. This research use 35 employees at PT. Asuransi Umum Bumi Putera Muda Unit Syariah Surabaya as a sample. Data collection use observations, interviews and (primary) questionnaires. This research uses data analysis of validity, reliability, classic assumption, and hypothesis tests. Data were analyzed by multiple linear regression with SPSS. This research shows that competence and work motivation simultaneously have a significant influence on employee performance. Partially, competence has positive and significant on employee performance. The result shows that the competencies possessed by the employee have an impact on employee performance. As well as role work motivation has positive and not significant on employee performance. The results of data testing show that the work motivation provided by the company has no impact on employee performance. The company must facilitate employees to increase competence and work motivation since employee performance correlates with firm performance.